THE IMPACT OF ARTIFICIAL INTELLIGENCE TOOLS ON ENGLISH LANGUAGE LEARNING - Tosheva Hanifa Istamovna (TADQIQOTLAR, 2026)
The rapid advancement of Artificial Intelligence (AI) has brought significant changes to the field of language education, particularly in English language learning. This paper explores the impact of AI-powered tools on learners’ linguistic development, motivation, and learning efficiency. By examining adaptive learning platforms, AI-driven chatbots, speech recognition systems, and automated assessment tools, the study highlights both the pedagogical benefits and potential limitations of AI integration. The findings suggest that AI technologies can substantially enhance English language learning when used as a complementary tool alongside traditional teaching methods.